Taking up McLuhan's cause : perspectives on media and formal causality - Anton, Corey; Logan, Robert K., 1939-; Strate, Lance (Intellect, 2017)
This book brings together a number of prominent scholars to explore a relatively under-studied area of Marshall McLuhan's thought: his idea of formal cause and the role that formal cause plays in the emergence of new technologies and in structuring societal relations.